Investigation of arsenic removal from aqueous solution through selective sorption and nanofiber-based filters - Domincova Bergerova, Eva; Kimmer, Dusan; Kovarova, Miroslava; Lovecka, Lenka; Vincent, Ivo; Adamec, Vladimir; Kobolova, Klaudia; Sedlarik, Vladimir (Journal of environmental health science & engineering, 2021)
BACKGROUND: This research paper focuses on removing of arsenic from contaminated water via a nanofibrous polymeric microfiltration membrane, applied in prospective combination with an inorganic sorbent based on iron oxide hydroxide FeO(OH). MATERIALS AND METHODS: Nanofibrous materials were prepared by electrospinning from polyurethane selected by an adsorption test. The chemical composition (FTIR), morphology (SEM, porometry) and hydrophilicity (contact angle) of the prepared nanostructured material were characterized. The process of eliminating arsenic from the contaminated water was monitored by atomic absorption spectroscopy (AAS). The adsorption efficiency of the nanofibrous material and the combination with FeO(OH) was determined, the level of arsenic anchorage on the adsorption filter was assessed by a rinsing test and the selectivity of adsorption in arsenic contaminated mineral water was examined. RESULTS: It was confirmed that the hydrophilic aromatic polyurethane of ester type PU918 is capable of capturing arsenic by complexation on nitrogen in its polymer chains. The maximum As removal efficiency was around 62 %. Arsenic was tightly anchored to the polymeric adsorbent. The adsorption process was sufficiently selective. Furthermore, it was found that the addition of even a small amount of FeO(OH) (0.5 g) to the nanofiber filter would increase the efficiency of As removal by 30 %. CONCLUSIONS: The presented results showed that an adsorption filter based on a polyurethane nanostructured membrane added with an inorganic adsorbent FeO(OH) is a suitable way for the elimination of arsenic from water. However, it is necessary to ensure perfect contact between the surface of the nanostructure and the filtered medium.
Keywords: Polyurethane; Arsenic; Iron oxide hydroxide; Adsorptive filtration